Education on the Arabic Language at the Time of the Qur'an's Revelation to Enhance Community Islamic Literacy - Andi Bangsawan Tolere; Kamaluddin Abu Nawas; Andi Abdul Hamzah (Yayasan Rahmat Islamiyah, 2026)
This Community Partnership Program (PKM) aims to strengthen the community's Islamic literacy through education on the characteristics of the Arabic language during the period of the Quran's revelation and its contribution to the development of Islamic civilization. The program was designed to enhance participants' understanding of the historical development of the Arabic language, the linguistic uniqueness of the Quran, and the importance of Arabic in understanding Islamic teachings. The PKM employed an educational approach consisting of lectures, interactive discussions, question-and-answer sessions, and the distribution of learning materials. The implementation demonstrated that participants' knowledge and awareness of the significance of the Arabic language in Islamic scholarship improved considerably. Participants also gained a better understanding of how the Quran transformed Arabic into the language of revelation, scholarship, and civilization, while introducing the foundations of linguistic sciences such as nahwu, sarf, balaghah, and tafsir lughawi. The program concludes that community-based educational activities can effectively improve Islamic literacy and encourage greater appreciation of the Arabic language as an essential medium for understanding the Quran and preserving the continuity of the Islamic intellectual heritage.